Cover Image. Issue 12 (14th December 2022) - Kondo, Keisuke; Isono, Hiroki
Abstract : The cover image is based on the Case Study A case of angle‐closure glaucoma caused by spontaneous lens dislocation by Hiroki Isono and Keisuke Kondo, https://doi.org/10.1002/ccr3.6670 .